中国“北极利益攸关者”身份建构——理论与实践 - 董利民 (2017)
身份的重要性在于群体成员的"我者群体"身份越强烈,越容易促使其加强"我者群体"与"他者群体"之间的区别,并导致对"他者群体"的歧视乃至排斥。目前中国在参与北极事务过程中被一些国家赋予的"非北极国家"等身份,是"北极国家"对参与北极事务的国家群体进行分类的结果,导致"非北极国家"的参与遭受质疑。中国政府于2015年冰岛"北极圈论坛"大会上首次向国际社会强调自己作为"北极利益攸关者"的身份。以"利益攸关者"展现自己并参与北极事务,有助于打破"我者—他者"二元身份逻辑,突破既有的"北极国家—非北极国家"二元对立划分方式。加强在"利益攸关者"这一集体身份下的认同,还有助于推动各方增信释疑、促进合作。身份建构是内在建构与外在承认的统一体。中国符合"北极利益攸关者"的构成标准。中国正在推动"北极利益攸关者"身份的内在建构,并积极争取获得更多外在承认。中国还需要努力成为"负责任的北极利益攸关者"。 We maintain or enhance our self-esteem by maximizing differences between our group and other groups on dimensions that positively reflect traits of our group. It appears that the more we identify with our group, the more likely we are to discriminate against out-groups. China＇s ＂non-Arctic states＂ identity leads to the discrimination by Arctic States. Chinese representatives has emphasized that China is a major stake- holder in the Arctic at Arctic Circle Assembly, 2015. It will be more beneficial to strengthen cooperation if we view all participants as ＂Arctic Stakeholders＂. The construction of identity consists of internal construc- tion and external recognition. China conforms to standards of ＂Arctic Stakeholders＂, and China is trying to gain more external recognition. Furthermore, China also needs to play the role of a responsible Arctic Stake- holder. 国家社科基金重点项目“国际法视角下的中国北极航线战略研究”(13AZD084)的阶段性研究成果；